The Contribution of Sukuk Placement and Securities to The Islamic Bank Profitability - Lucky Nugroho; Ahmad Badawi; Nurul Hidayah (Tazkia Islamic Finance and Business Review, 2019)
The purpose of this study was to determine the effect of the placement of Islamic bank funds on government assets, the placement of Islamic bank funds at the central bank and the influence of Islamic bank funds on non-government assets on the profitability of Islamic banks. The method is quantitative with a multiple regression statistical model and the Stata version 13 as the statistical software. Based on data processing on research variables it was found that investment in state sukuk had a negative and significant effect on return on assets. Furthermore, the variable investment in securities in Bank Indonesia instruments has a positive and significant impact, while investment in sukuk corporates has a positive effect that is not significant. Therefore Sharia Banks must be able to select investment options in placing their excess funds to maintain bank reputation and performance so that public trust increases with the functions and contributions of Islamic banks.